Amplified ribosomal DNA restriction analysis and Random amplified polymorphic DNA analysis: useful genetic markers for mycoparasite diagnostics in edible mushrooms - Sharma, V P; Kamal, Shwet; Kumar, Satish (Mushroom Research, 2015)
Three arbitrary decamer RAPD primers amplified unique scorable DNA fragments and exhibited variations among different mycoparasites of edible mushrooms. Taq 1 restriction enzyme produced unique Amplified Ribosomal DNA Restriction Analysis (ARDRA) profiles in four important mycoparasites, namely, Hypomyces perniciosus (200bp), Cladobotryum asterophorum (280bp), Cladobotryum mycophilum (300bp), and Papulospora byssina (400bp). Whereas, Msp 1 restriction enzyme yielded unique profiles for identification of Chaetomium globosum (440bp), Trichoderma harzianum (380bp), Trichoderma longibrachiatum (300bp), and Sepedonium chryospermum (350bp), that can be usedÂ as genetic markers for quick detection of these mycoparasites without resorting each time to DNA sequencing.